2021
DOI: 10.5455/aim.2021.29.32-37
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Between Surgical and Nonsurgical Intussusception: A Diagnostic Model Using Multi-Detector Computed Tomography

Abstract: Background: The differentiation of surgical from nonsurgical adult intussusception may enable the appropriate selection of management strategies. Objective: This study aimed to investigate the diagnostic potential of multidetector computed tomography (MCDT) features to differentiate surgical from nonsurgical adult intussusception and develop a diagnostic model. Methods: A retrospective study was performed on 96 patients with intussusceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…The length of intussusception was reported as a feature to distinguish self-limiting intussusception from these requiring surgery. 11,13,21 Most authors argued that intussusceptions ≥5 cm in length should be treated with surgery. These studies did not consider the enteroscopic treatment as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…The length of intussusception was reported as a feature to distinguish self-limiting intussusception from these requiring surgery. 11,13,21 Most authors argued that intussusceptions ≥5 cm in length should be treated with surgery. These studies did not consider the enteroscopic treatment as an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…8,14 Transient symptomatic intussusception (TSI) Numerous authors have reported the spontaneous resolution of intussusception in children 5,9,14,[21][22][23] and adults. 8,10,12,13,[25][26][27][28][29][30] In some patients, resolution of symptoms may occur before any management decisions are made. 9,14,23 In other patients who are stable and exhibit mild symptoms and encouraging imaging findings, a decision to offer expectant management can be made.…”
Section: Imagingmentioning
confidence: 99%
“…This is particularly the case if an intussusception is found on CT imaging because the finding may be reported without placing it in the context of the patient's symptomatology and the finding of transient intussusception may be incidental and unrelated to the patient's presenting symptoms. 8,12,13,27 Ultrasound has the distinct advantage of having direct patient contact, allowing the sonographer to perform sonopalpation and correlate the imaging appearance to the patient's symptoms. 23 Ultrasound is also well placed as a surveillance tool for intussusception due to the lack of ionising radiation.…”
Section: Transient Asymptomatic Intussusception (Tai)mentioning
confidence: 99%
See 1 more Smart Citation
“…Generalize peritonit, perforasyon, kanlı dışkılama ve yüksek dereceli lökositozun olduğu gecikmiş vakalarda cerrahi tedavi esastır. Bizim hastaların ise 42'sinde (% 26,9) cerrahi tedavi gerekti ve bu oran literatürden daha yüksekti (12). Cerrahi tedavi gereken hastaların çoğu <2 yaş hastalar ve ileoileal invajinasyonu (28 hasta ve %66,7) olan hastalardı.…”
Section: Bulgularunclassified